The effectiveness of industrial development strategy in Ethiopia - Jagemma, Milkessa; Worku, Hailu (The journal of contemporary issues in business and government, 2021)
Prioritizing the development of fastidious sectors or regions is habitually part of Least Developed Countries Development Approaches. We study a consummate example of such policies in Ethiopia, using geographic and sectoral disparity in the form and scale of the policy for recognition. Using analytical outline of policy-related principles, criteria and indicators (PCI) we show that the policy was disastrous: There was no improvement in productivity, productive assets, or employment. The strategy failed due to low legitimacy of industry development policy from the existing stakeholders. Lastly, result indicates that due to skills gaps, budget, unapparent guide lines, the rate of industrial development was declined by 25 percent.